1996
DOI: 10.1097/00007890-199612270-00009
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Prospective Multicenter Pharmacoepidemiologic Study of Cyclosporine Microemulsion in Stable Renal Graft Recipients1,2,3

Abstract: MeCsA appears to be a safe and effective therapy in stable renal transplant patients and provides superior and more consistent absorption of cyclosporine when compared with ConCsA. Transient toxicity after conversion to MeCsA occurs in some patients, and may reflect the increased exposure to cyclosporine. Use of a limited sampling approach combining trough and 2-hr postdose concentrations may provide an effective way to monitor this exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(57 citation statements)
references
References 12 publications
5
49
1
2
Order By: Relevance
“…Studies performed early after transplantation and also in stable patients, in different types of organ transplantation, have consistently shown improved dose-concentration linearity, reduced between-subject and within-subject variability, stronger concentration-AUC correlations and an improved efficacy/toxicity/tolerability profile [3,14,17,21,22,23,37,38,431. Compared with the oil-based formulation, the higher Cmax and AUC achieved with the microemulsion formulation [7] provide higher exposure, which has been associated with reduced, but still significant, acute rejection rates of 35% in patients receiving cyclosporine, azathioprine, and prednisone [21, 411. Concurrently, many studies have been performed to perfect therapeutic cyclosporine monitoring after transplantation [7,9,10,35,401.…”
Section: Introductionmentioning
confidence: 99%
“…Studies performed early after transplantation and also in stable patients, in different types of organ transplantation, have consistently shown improved dose-concentration linearity, reduced between-subject and within-subject variability, stronger concentration-AUC correlations and an improved efficacy/toxicity/tolerability profile [3,14,17,21,22,23,37,38,431. Compared with the oil-based formulation, the higher Cmax and AUC achieved with the microemulsion formulation [7] provide higher exposure, which has been associated with reduced, but still significant, acute rejection rates of 35% in patients receiving cyclosporine, azathioprine, and prednisone [21, 411. Concurrently, many studies have been performed to perfect therapeutic cyclosporine monitoring after transplantation [7,9,10,35,401.…”
Section: Introductionmentioning
confidence: 99%
“…Some study concluded that it's better to start absorption profiling to prevent any nephrotoxicity and It declared that the mixture of C0 and C2 (C2/C0 or CA) provided good correlation with AUC 0-12 (70). However, literatures in this field are rare and seems that Pharmacodynamics policies and Prospective Randomized clinical trials is needed to be designed to address this question.…”
Section: Relative Importance Of Attaining Cyclosporine Absorptionmentioning
confidence: 99%
“…The current knowledge on cyclosporine pharmacogenetics comes from studies in recipients of solid organ transplants. Bioavailability and clearance of the drug are inluenced by polymorphic P-glycoprotein (ABCB1) in gastrointestinal tract and CYP3A4 and CYP3A5 in the liver, suggesting that these polymorphisms could also inluence the response to cyclosporine treatment in psoriatic patients [27,28]. There was only one pharmacogenetic study performed on psoriasis patients treated with cyclosporine, and it focused only on ABCB1 polymorphisms ( Table 2).…”
Section: Cyclosporinementioning
confidence: 99%